Study and analysis of soft grippers for assembly tasks - Tan, Hong Wei (Nanyang Technological University, 2024)
Soft grippers have garnered significant attention in industrial applications due to their versatility and adaptability in handling objects with complex shapes and varying properties. Traditional rigid grippers present difficulties in handling thin and flexible workpieces, particularly clothing in polybags due to their inherent flexibility and potential sagging of the bags. This study delves into the design and evaluation of a soft gripper tailored for manipulating items in flexible packaging, with a focus on clothing in polybags. By employing a two-staged gripping strategy that consists of a suction cup, coupled with soft robotic components such as soft linear vacuum actuators and PneuNets bending actuators, the gripper was designed and fabricated. Through rigorous testing and evaluation, the gripper not only demonstrated proficiency in handling clothing in thin and flexible packaging, but it also managed to pick up tightly stacked items and grasp a wide variety of objects with diverse geometries. This study offers insights into the potential and feasibility of soft grippers in industrial settings.